Pemanfaatan media sosial dalam peningkatan keterampilan membaca dan mendengar bahasa Rusia bagi mahasiswa - Dewi, Anggraeni Purnama; Rachmat, Ani (Fakultas Sastra, 2023)
Currently Russian is one of the most popular foreign languages in Indonesia, because of its large role in various fields of life, such as education, economy, culture, tourism, military, and so on. However, it cannot be denied that the Russian language has a fairly high level of complexity, so it requires perseverance and patience from the learner. This is a challenge for students to master Russian and be proficient in using it. This study aims to find out how much students use social media as a means of supporting learning, especially in terms of reading and listening to Russian. In addition, it is intended to find out the development of students after studying through social media. The method used is qualitative with descriptive presentation. The results showed that of the 48 respondents, 79% felt the benefits of social media as a means of improving their reading and listening skills in Russian, while the other 21% did not feel a significant improvement in their learning process. Keywords: social media, reading & listening skills, Russian language